Oral delivery of solid lipid nanoparticles: underlining the physicochemical characteristics and physiological condition affecting the lipolysis rate. (2nd November 2021) - Mahmoudian, Mohammad; Maleki Dizaj, Solmaz; Salatin, Sara; Löbenberg, Raimar; Saadat, Maryam; Islambulchilar, Ziba; Valizadeh, Hadi; Zakeri-Milani, Parvin
ABSTRACT: Introduction: Lipid-based nano-drug delivery systems (LBNDDSs) have gained widespread attention in oral drug delivery due to their tunable and versatile properties such as biocompatibility and biodegradability, which makes them promising delivery systems for a variety of therapeutics. Currently, different types of LBNDDSs including liposomes, micelles, nanoemulsions, and solid lipid nanoparticles (SLNs) are developed for drug delivery applications. SLNs can be used as a controlled drug delivery system for oral delivery applications. However, its lipidic context makes that susceptible to lipolysis. The lipolysis rate of SLNs is affected by many factors that raise many questions for developing a more efficient delivery system Areas covered: In the present work, we highlighted different factors affecting the digestion rate/level of SLNs in the gastrointestinal tract. This paper can be most useful for those researchers who are keen to develop a properly controlled drug delivery system based on SLNs for oral delivery applications. Expert opinion: SLNs can be used as a controlled drug delivery system for oral delivery applications. However, its lipidic context makes that susceptible to lipolysis. The lipolysis rate of SLNs is affected by many factors that raise many questions for developing a more efficient delivery system.